公民科學家意象與參觀博物館對科學研究利益知覺之影響 Influence of Citizens' Images of Scientists and Museum Visits on the Benefit Perception - 黃孝宗 Hsiao-Tsung Huang; 蔡俊彥 Chun-Yen Tsai; 黃台珠Tai-Chu Huang (National Taiwan Normal University, 2013)
科學與技術研究常伴隨著社會性科學議題的產生，公眾於這些議題中對各項科學研究利益知覺（簡稱「科學知覺」）被認為是一項科學素養的指標。本研究主要目的在於探討公民的科學家意象與有無參觀博物館對科學知覺的影響。研究工具採用「公民科學素養問卷」，以「機率比例抽樣法」抽出研究對象，並以實地訪談調查研究法完訪臺灣地區公民2,024 人。分析方法採量化研究，以階層迴歸分析法檢驗。研究結果發現，科學家意象及參觀博物館對公民科學知覺有預測力，科學家意象愈無刻板印象及1 年內有參觀博物館的公民，其科學知覺愈正向。以有無參觀博物館為調節變項，發現1 年內沒有參觀博物館的公民，科學家意象對科學知覺的預測效果較大；1年內有參觀博物館的公民，科學家意象對科學知覺的預測效果較小。研究建議，科學教育學者應重視公民對科學家的刻板印象，以及促進公民參觀博物館，以期公民能夠有正向的科學知覺。 Science and technology research addresses various socio-scientific issues. The benefit perception of scientific research (BPSR) is a crucial indicator of scientific literacy. The purpose of this study is to explore the effects of citizens' images of scientists and museum visits on the BPSR. Participants for this study (2,024 in total) were obtained through a probability-proportional-to-size sampling method and were interviewed using the Civic Scientific Literacy Survey. A quantitative analysis was conducted through hierarchical regression analyses. The results showed that images of scientists and museum visits revealed predictability to the BPSR among Taiwanese citizens. The fewer stereotypes that Taiwanese citizens possess about scientists, the greater is the perceived benefits of scientific research. Those who had visited museums in the past year perceived more benefits from scientific research. When museum visit was used as the moderating variable, it revealed two levels of regression. Among the citizens who had not visited museums in the past year, the effect of images of scientists on their BPSR was strong. By contrast, among people who had visited museums in the past year, the effect of images on their BPSR was weak. The research suggests that science educators emphasize citizen stereotypes of scientists and promotion of the visits to science museums. This may allow citizens to perceive the benefits of scientific research.